The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/00365521.2013.833647
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fasting and post-prandial plasma bile acid responses after Roux-en-Y gastric bypass surgery

Abstract: Weight loss following RYGB is associated with an increase in post-prandial plasma BA response due to larger amounts of glycine-conjugated BAs. This suggests up regulation of BA production and conjugation after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 39 publications
6
41
2
1
Order By: Relevance
“…Regardless, Ahmad et al (29) showed that even if fasting plasma bile acid concentrations are unchanged after bariatric surgery, the response to a meal appears to be restored to that of a healthy, lean individual. Nonetheless, the increases seen at 15 months by Werling et al (28) in fasting bile acids are similar to our results for total and unconjugated bile acids. The changes reported in primary bile acids are mixed compared to the current study because they report increases in CDCA but not CA, whereas we see increases in both.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regardless, Ahmad et al (29) showed that even if fasting plasma bile acid concentrations are unchanged after bariatric surgery, the response to a meal appears to be restored to that of a healthy, lean individual. Nonetheless, the increases seen at 15 months by Werling et al (28) in fasting bile acids are similar to our results for total and unconjugated bile acids. The changes reported in primary bile acids are mixed compared to the current study because they report increases in CDCA but not CA, whereas we see increases in both.…”
Section: Discussionsupporting
confidence: 94%
“…Most early reports describing the changes in bile acid concentrations postoperatively do not detail the individual concentrations and tend to group chemically similar bile acids (eg, primary/secondary, conjugated/unconjugated) for analysis. The largest (n ϭ 63) and most comprehensive study to date by Werling et al (28) examined chemical groups and individual bile acids in the fasted and postprandial states. This study showed increases in fasting total and unconjugated bile acids, which is similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, LSG exerted the least evident effect on postoperative serum BA levels. According to some authors, the postsurgery increase in serum BAs was associated with an improvement of glucose metabolism [15,[21][22][23][24]. Our findings are consistent with those data, since the levels of serum glucose, insulin, HOMA, and HBA1c at 3 months after the bariatric procedure were significantly lower than those prior to the surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Most short-term studies (< 2 months after surgery) report unchanged or decreased levels of total BAs [26][27][28], while most studies reporting data from several months and years after surgery report increased concentrations [18,20,[29][30][31][32]. Our findings are in accordance with the existent literature, and extend the current knowledge by showing that the BA levels apparently continue to increase up to 5 years after RYGB.…”
Section: Discussionsupporting
confidence: 83%